2015
DOI: 10.1159/000370123
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Open-Label Study to Assess the Efficacy and Safety of a Herbal Medicinal Product (Sinupret) in Patients with Acute Rhinosinusitis

Abstract: Aims: We present a multicenter, prospective, open-label study to assess the efficacy and safety of a phytomedicine. The aim of the research was to evaluate the efficacy and safety of 14 days of treatment with Sinupret for acute rhinosinusitis. Sinupret is a herbal preparation used to restore and maintain the physiological function of the membranes in the sinus cavity. Methods: Sixty patients with acute rhinosinusitis based on the EPOS guidelines were enrolled in the study. Thirty patients were treated with Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 2 publications
0
9
0
8
Order By: Relevance
“…In addition, a recent prospective, placebo-controlled study with 386 patients demonstrated the effectiveness of phytopharmaceuticals with several components in comparison with placebo [114]. Another open trial recently confirmed these results [115]. …”
Section: Types and Therapies Of Rhinosinusitismentioning
confidence: 99%
“…In addition, a recent prospective, placebo-controlled study with 386 patients demonstrated the effectiveness of phytopharmaceuticals with several components in comparison with placebo [114]. Another open trial recently confirmed these results [115]. …”
Section: Types and Therapies Of Rhinosinusitismentioning
confidence: 99%
“…Следует отметить растительный препарат с доказанной эффективностью -препарат Синупрет ® . Эффективность препарата была подтверждена в клинических исследованиях, в которых он применялся как раз как вспомогательное средство лечения острого и хронического РС у взрослых и у детей [9]. Tcanecu с соавт.…”
Section: терапияunclassified
“…А по данным ряда авторов, активность препарата сопоставима с эффективностью назальных кортикостероидов относительно ОРС, в частности флутиказона фуроата. При этом в основной группе в отличие от группы ИНГКС, где отмечались легкие побочные эффекты, нежелательных явлений зарегистрировано не было [30].…”
Section: патогенетическая терапия направленная на купирование назальunclassified